Currency Hedging for International Portfolios - Schmittmann, Jochen M. (Washington, D.C. : International Monetary Fund, 2010)
This paper examines the benefits from hedging the currency exposure of international investments in single- and multi-country equity and bond portfolios from the perspectives of German, Japanese, British and American investors. Over the period 1975 to 2009, hedging of currency risk substantially reduced the volatility of foreign investments at a quarterly investment horizon. Contrary to previous studies, the paper finds that at longer investment horizons of up to five years the case for hedging for risk reduction purposes remained strong.In addition to its impact on risk, hedging affected returns in economically meaningful magnitudes in some cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet